STARD for Abstracts: essential items for reporting diagnostic accuracy studies in journal or conference abstracts - Cohen, J; Korevaar, D; Gatsonis, C; Glasziou, P; Hooft, L; Moher, D; Reitsma, J; De Vet, H; Bossuyt, P; Stard Group,; Heneghan, C (BMJ Publishing Group, 2017)
Many abstracts of diagnostic accuracy studies are currently insufficiently informative. We extended the STARD (Standards for Reporting Diagnostic Accuracy) statement by developing a list of essential items that authors should consider when reporting diagnostic accuracy studies in journal or conference abstracts. After a literature review of published guidance for reporting biomedical studies, we identified 39 items potentially relevant to report in an abstract. We then selected essential items through a two round web based survey among the 85 members of the STARD Group, followed by discussions within an executive committee. Seventy three STARD Group members responded (86%), with 100% completion rate. STARD for Abstracts is a list of 11 quintessential items, to be reported in every abstract of a diagnostic accuracy study. We provide examples of complete reporting, and developed template text for writing informative abstracts.